1986
DOI: 10.1111/j.1745-9125.1986.tb01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Stitch and Sew: The Impact of Medical Resources Upon Criminally Induced Lethality

Abstract: One theoretical explanation for the consistently high Southern homicide rates is that the South constitutes a “regional culture of violence.” Although this perspective has not garnered much empirical support, sound theoretical alternatives have not emerged. The present study attempts to fill this gap by suggesting that emergency medical services are an overlooked intervening influence in the production of homicide and aggravated battery rates. Analysis of data from the 67 counties in Florida provides some supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Levels of felonious killings of officers have been attributed to some factors that represent agency context, such as region (Boylen & Little, 1990;Kaminski, Jefferis, & Chanhatasilpa, 2000), population characteristics (Chamlin, 1989;Kaminski, Jefferis, & Gu, 2003), economic disadvantage or disparity (Jacobs & Carmichael, 2002;Kaminski & Marvell, 2002;Lester, 1987;Peterson & Bailey, 1988), violent crime (Fridell & Pate, 1995;Jacobs & Carmichael, 2002;Kaminski et al, 2003), emergency medical services (Doerner & Speir, 1986), and to factors representing agency policy and practice, such as better tactics and safety-facilitating policies/procedures, and the use of soft body armor (Bristow, 1963;Federal Bureau of Investigation, 1992;Fyfe, 1987;Konstantin, 1984;Sherman, DeRiso, Gaines, Rogan, & Cohn, 1989). Kaminski (2002) drew upon routine activities theory to examine the factors that impact on levels of violence against police.…”
Section: Correlates Of Police Victimizationmentioning
confidence: 98%
“…Levels of felonious killings of officers have been attributed to some factors that represent agency context, such as region (Boylen & Little, 1990;Kaminski, Jefferis, & Chanhatasilpa, 2000), population characteristics (Chamlin, 1989;Kaminski, Jefferis, & Gu, 2003), economic disadvantage or disparity (Jacobs & Carmichael, 2002;Kaminski & Marvell, 2002;Lester, 1987;Peterson & Bailey, 1988), violent crime (Fridell & Pate, 1995;Jacobs & Carmichael, 2002;Kaminski et al, 2003), emergency medical services (Doerner & Speir, 1986), and to factors representing agency policy and practice, such as better tactics and safety-facilitating policies/procedures, and the use of soft body armor (Bristow, 1963;Federal Bureau of Investigation, 1992;Fyfe, 1987;Konstantin, 1984;Sherman, DeRiso, Gaines, Rogan, & Cohn, 1989). Kaminski (2002) drew upon routine activities theory to examine the factors that impact on levels of violence against police.…”
Section: Correlates Of Police Victimizationmentioning
confidence: 98%
“…The results were mixed. Using as independent variables countywide measures of structural poverty (Loftin & Hill, 1974) and medical resources, Doerner and Speir (1986) extended Doerner's 1983 study by looking at homicide in Florida's 67 counties from 1968 to 1972. As their main dependent variable, Doerner and Speir used a new variable they constructed called percent lethality, or simply the ratio of recorded homicide cases to the number of recorded homicide and aggravated assaults.…”
Section: The Impact Of Medical Advances On Homicide and Aggravated Asmentioning
confidence: 98%
“…Although not explicitly concerned with describing or explaining national historical trends involving the aggravated assault/ homicide paradox, previous criminological research that examines the link between medical resources and homicide, particularly Doerner's work (1983Doerner's work ( , 1988Doerner & Speir, 1986), provides a critical building block in our analysis (see also Barlow & Barlow, 1988;Giacopassi, Sparger, & Stein, 1992;Long-Onnen & Cheatwood, 1992). Relying on this research, we think the best starting point in explaining the homicide paradox involves the observation of parallel, dramatic developments in medical technology and related support services, 2 developments that may have functionally, and equally dramatically, suppressed the homicide rate compared to what it would be had such progress not been made.…”
mentioning
confidence: 98%
“…An enormous corpus of research employing diverse sources of data and analytical methods demonstrated that crime rates were dramatically lower in rural locations compared to urban and suburban areas. Moreover, phenomena such as violent crime, delinquent gangs, and fear of crime were appreciably lower in rural areas and among rural citizens (Bachman, 1992;Clinard, 1944;Doerner & Speir, 1986;Fagan, Piper, & Moore, 1986;Gibbons, 1972;Laub, 1981Laub, , 1983Miller, Hoiberg, & Ganey, 1982;Smith & Huff, 1982;Weisheit & Donnermeyer, 2000;Weisheit & Wells, 1999).…”
Section: Introductionmentioning
confidence: 97%